2004
DOI: 10.1556/avet.52.2004.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplementation with methionine and different fat sources on the glutathione redox system of growing chickens

Abstract: The effect of supplementary methionine and fats of different saturation levels on the glutathione redox system of growing broiler cockerels was studied. The diet of three groups of chicks was supplemented with corn germ oil, beef tallow and fish oil at the levels of 30 g/kg and 50 g/kg of feed, respectively. The diet of further three groups was supplemented with methionine (5 g/kg of feed) in addition to the different fat sources. Control chicks were fed with a compound feed without methionine and fat suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…The increased GSH-Px activity was possibly caused by the higher substrate (GSH) content in the same group as was also found in our previous experiment (Németh et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…The increased GSH-Px activity was possibly caused by the higher substrate (GSH) content in the same group as was also found in our previous experiment (Németh et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…the actual supply of methionine and cysteine (Németh et al, 2004). The amino acid content of the diets was near the same in both groups which means that DDGS with higher proportion of PUFA, therefore higher susceptibility to oxidation, may provoke lipid peroxidation.…”
mentioning
confidence: 88%
“…25,37,47) Our results showed that hepatic GSH, which was measured after intoxication with acetaminophen, was significantly lower in soybean oil fed animals than counterpart of those groups (Fig. 1).…”
Section: Discussionmentioning
confidence: 64%